2003
DOI: 10.1007/s00424-003-1096-x
|View full text |Cite
|
Sign up to set email alerts
|

A new view of K+-induced contraction in rat aorta: the role of Ca2+ binding

Abstract: Strong, K+ -induced contractions of rat aorta in Ca-free, Mg-free media were not accompanied by increased intracellular calcium concentration, [Ca2+](i), whereas such contractions in the presence of the divalent cations were correlated with rising [Ca2+](i) as assessed by fura-2. At the same time, calcium channel blockers, a modulator of Ca2+-binding proteins, and a modulator of actin polymerization, inhibited all types of K+ -induced contractions. Increasing the K+ in isotonic medium evoked a rise of (45)Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, Kravtsov and co-workers reported that K + o -induced contractions in Mg 2+ -free medium are not mediated by Ca 2+ -influx and occur in the presence of EDTA [30]. It should be underlined, however, that in contrast to shrunken VSMR, K + o -induced contractions in Mg 2+ -free medium were suppressed by L-type channel blockers [30].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, Kravtsov and co-workers reported that K + o -induced contractions in Mg 2+ -free medium are not mediated by Ca 2+ -influx and occur in the presence of EDTA [30]. It should be underlined, however, that in contrast to shrunken VSMR, K + o -induced contractions in Mg 2+ -free medium were suppressed by L-type channel blockers [30].…”
Section: Discussionmentioning
confidence: 80%
“…Thus, Kravtsov and co-workers reported that K + o -induced contractions in Mg 2+ -free medium are not mediated by Ca 2+ -influx and occur in the presence of EDTA [30]. It should be underlined, however, that in contrast to shrunken VSMR, K + o -induced contractions in Mg 2+ -free medium were suppressed by L-type channel blockers [30]. It was shown that Ca 2+ o -independent VSMC contractions triggered by activators of protein kinase C, tyrosine and Rhoassociated kinases were mediated by calcium sensitization of the contractile machinery [8,23,38].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contraction in vascular smooth muscle can be initiated by mechanical, electrical, and chemical stimuli. Electrical depolarization of the vascular smooth muscle cell membrane (as produced by 80 mM KCl) elicits contraction by increasing the intracellular Ca 2+ concentration, most likely by opening voltage dependent Ca 2+ channels (L-type Ca 2+ channels) (10). Accumulating evidence suggests that the transient receptor potential (TRP) channels modulate the driving force for Ca 2+ entry through L-type Ca 2+ channels and provide intracellular pathways for Ca 2+ release from cellular organelles, thus increasing the intracellular Ca 2+ concentration (11).…”
Section: Discussionmentioning
confidence: 99%